Kegiatan Employee Relations yang dilakukan oleh Kedai Lyke Eat - Muhammad Arie Syahrial Sadikin (Bandung Conference Series: Public Relations, 2022)
Abstract. Lyke Eat shop is a micro, small and medium enterprise or commonly abbreviated as MSME. Lyke Eat shop is one of the SMEs that has good employee relations. Employee relations here is the relationship between the owners and their employees. The owners choose employee relations through interpersonal communication. Because interpersonal communication is personal and involves feelings. Therefore, the purpose of this study is to determine employee relations activities through interpersonal communication by the owners to their employees. The approach used in this research is a qualitative approach with a case study method. The theory used is the theory of social interaction and internal communication. Data collection techniques used are observation, interviews, and documentation. Data analysis techniques used are data reduction techniques, data presentation, and drawing conclusions. The last process is to test the validity of the data or the validity of the data through triangulation of sources. The result of the research is that interpersonal communication steps in employee relations activities, the owners approach character by using social interaction. Integrating the employee relations activity plan they have with their interpersonal communication implementation plan, the owners use internal communication, specifically vertical communication, to overcome the bad effects. The reason for using interpersonal communication in employee relations activities is because the owners consider this interpersonal communication important because it is a form of communication that can make employee relations well formed, very effective, easy to implement, and can also accelerate the process of closeness and trust. Abstrak. Kedai Lyke Eat merupakan usaha mikro, kecil, dan menengah atau biasa disingkat UMKM. Kedai Lyke Eat merupakan salah satu UMKM yang memiliki employee relations yang baik. Employee relations disini merupakan hubungan antara para owner dengan para pegawainya. Para owner memilih employee relations melalui komunikasi interpersonal. Karena komunikasi interpersonal bersifat pribadi serta melibatkan perasaan. Maka dari itu tujuan dari penelitian ini untuk mengetahui kegiatan employee relations melalui komunikasi interpersonal oleh para owner terhadap para pegawainya. Pendekatan yang digunakan dalam penelitian ini adalah pendekatan kualitatif dengan metode studi kasus. Teori yang digunakan adalah teori interaksi sosial dan komunikasi internal. Teknik pengumpulan data yang digunakan adalah observasi, wawancara, dan dokumentasi. Teknik analisis data yang digunakan adalah teknik reduksi data, penyajian data, dan penarikan kesimpulan. Proses terakhir yaitu uji keabsahan data atau validitas data melalui triangulasi sumber. Hasil dari penelitian adalah langkah komunikasi interpersonal dalam kegiatan employee relations para owner melakukan pendekatan karakter dengan menggunakan interaksi sosial. Mempadukan rencana kegiatan employee relations yang dimiliki dengan rencana pelaksanaan komunikasi interpersonalnya, para owner menggunakan komunikasi internal tepatnya komunikasi vertikal untuk mengatasi dampak buruknya. Alasan menggunakan komunikasi interpersonal dalam kegiatan employee relations dikarenakan para owner menganggap komunikasi interpersonal ini penting karena salah satu bentuk komunikasi yang dapat membuat employee relations terbentuk dengan baik, sangat efektif, mudah untuk dilaksanakan, dan juga dapat mempercepat proses kedekatan serta kepercayaan.